Evaluation of the protective effect of lycopene on growth performance, intestinal morphology, and digestive enzyme activities of aflatoxinB1 challenged broilers. (19th March 2021) - Sarker, Md Touhiduzzaman; Wang, Zhi Yue; Yang, Haiming; Wan, Xiaoli; Emmanuel, Asare
Abstract: The current study was conducted to investigate the protective efficiency of dietary lycopene (LYC) supplementation on growth performance, intestinal morphology, and digestive enzyme activities aflatoxinB1 (AFB1 ) challenged broilers. A total of 240 days old Arber across male broiler chicks were randomly allocated in five treatments and six replicates (eight birds per replicate); feed and water were provided ad libitum during the 42 days experiment. The treatment diets were as follows: (i) Basal diet (control), (ii) Basal diet + 100 µg/kg AFB1 contaminated diet, (iii) Basal diet + 100 µg/kg AFB1  + 100 mg/kg LYC1, (iv) Basal diet + 100 µg/kg AFB1  + 200 mg/kg LYC2, and (v) Basal diet + 100 µg/kg AFB1  + 400 mg/kg LYC3. The results showed that the addition of LYC to AFB1 contaminated broiler diets significantly increased ( p  < .05) average daily gain (ADG) and decreased feed conversion ratio (FCR) compared to the AFB1 diet. AFB1 diet decreased the intestinal villus height (VH) and crypt depth ratio (VCR) while increasing the crypt depth (CD). However, dietary LYC supplemented diets relieved the intestinal morphological alterations. Dietary LYC supplementation (200 and 400 mg/kg) significantly improved ( p  < .05) intestinal digestive enzyme amylase and lipase activities with AFB1 contaminated diet. These findings suggested that LYC is a promising feed supplement in the broiler industry, alleviating the harmful effects of AFB1 .